Global forecasting models for dengue outbreaks in endemic regions: a systematic review - Agung Sutriyawan; Mursid Rahardjo; Martini Martini; Dwi Sutiningsih; Cheerawit Rattanapan; Nur Faeza Abu Kassim (Журнал микробиологии, эпидемиологии и иммунобиологии)
Background. Dengue is a rapidly spreading mosquito-borne disease, posing significant global health challenges, particularly in endemic regions. Recent years have witnessed an increase in the frequency and intensity of dengue outbreaks, necessitating robust forecasting models for early intervention.